Russian social democracy in the Underground : a study of the RSDRP in the Ukraine, 1907-1914 - Elwood, Ralph Carter (Assen Amsterdam : Van Gorcum IISG, 1974)
Bibliotheek François Vercammen
Engels
Monografie